EKSISTENSI MAQÀSHID AL-SYARÌ’AH DALAM PEMBARUAN HUKUM PIDANA DI INDONESIA - Harahap, Zul Anwar Ajim (istinbath, 2017)
Abstract: This paper examines maqashid al-shariah in the Indonesian penallaw reform. Building on the theory of existence and maqashid al-shariah, thisnormative legal study explores elements and values of Islamic law withinthe national law. This study shows that Islamic law has influenced the Bill ofNational Penal Code since it was used as one important source of the code.The principles of maqashid al-shariah color the chapters of the Bill, especiallyin Book I on the general prescription and on Book II on criminal acts. Fromthe 49 chapters of the bill that are examined, it has been identified with thestrong values of maqashid. The stronger principle of the maqashid that isadopted is the protection of faith, followed by the protection of life, offspring,and reason. The least principle of the maqashid in the bill is the protection ofproperty because this part is closely related to civil matters. Abstrak: Tulisan ini menyajikan hasil penelitian tentang eksistensi maqàshid alsyarì’ahdalam pembaruan hukum pidana di Indonesia. Kajian ini diawali darieksistensi hukum Islam dalam tatanan hukum nasional di berbagai Undangundanguntuk mengungkapkan rumusan-rumusan yang ada dalam hukumIslam kemudian dibandingkan dengan rumusan dalam RUU KUHP. Hasilpenelitian menunjukkan bahwa hukum Islam telah eksis dalam RUU KUHPsebagai sumber dan bahan hukum nasional. Konsep maqàshid al-syarì’ah dalampembentukan hukum Islam menjadi dasar dalam perwujudannya. HukumIslam bertujuan untuk mewujudkan kemaslahatan manusia yang dicapaidengan cara memperoleh kemaslahatan bagi manusia dan menolak segalahal yang merusak kehidupan, baik di dunia maupun di akhirat. Kemaslahatantersebut adalah untuk memelihara kehidupan, jiwa, dan akal. Konsep terakhirmaqahsid adalah untuk memelihara harta karena penutup bagian ini dikaitkandengan masalah-masalah sosial.